Pengaruh Sistem Remunerasi Terhadap Motivasi Kerja, Kepuasan Kerja Dan Dampaknya Terhadap Kinerja Perawat - Hartono, Budi; Sulaeman, Suhendar; Nopianna, Inna; Sari, Komala (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Objective: to determine the effect of the remuneration system on work motivation, job satisfaction and its impact on nurse's performance in the Dr. M. Goenawan Partowidigdo Lung Hospital, Cisarua, Bogor.Methods: This article methode is a descriptive analysis which use partial data analysis least square. The source of data research by questionaire filled by the government and general services corporation nurses for 97 samples.Results: The result of this research has shown a significant influences between remuneration system to motivation, satisfaction services and also performance of nurses. It is proven that the result of Smart application Partial Least Square has shown us all the indicator result >0.6 with correlation value close to 1 and validity test in each indicator give the valid result >0.7. Conclusion: this hospital keeps continue using the remuneration system in order to give the division of payment services, give the transformation of leadership application program, block the social media situs program, lose the multitasking, optimize the supervision program, optimize the sport program to increase motivation, working and performance satisfaction of nurses.